Cell lineage-based stratification for glioblastoma - Wang, Zilai (Cancer Cell, 2020)
Glioblastoma, the predominant adult malignant brain tumor, has been computationally classified into molecular subtypes whose functional relevance remains to be comprehensively established. Tumors from genetically engineered glioblastoma mouse models initiated by identical driver mutations in distinct cells of origin portray unique transcriptional profiles reflective of their respective lineage. Here, we identify corresponding transcriptional profiles in human glioblastoma and describe patient derived xenografts with species-conserved subtype-discriminating functional properties. The oligodendrocyte lineage associated glioblastoma subtype requires functional ERBB3 and harbors unique therapeutic sensitivities. These results highlight the importance of cell lineage in glioblastoma independent of driver mutations and provide a methodology for functional glioblastoma classification for future clinical investigations.